Answer with explanation:
We know that any point located at (x,y)
Also, if the x-value and y-value both are positive then the point lie in first quadrant.
if both are negative then it lie in third quadrant.
If x-value is positive and y-value is negative then it lie in the fourth quadrant.
If x-value is negative and y-value is positive then it lie in the second quadrant.
The
![\sin \theta=(y)/(√(x^2+y^2))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1umcx5xwza16h7i2if2e1suowcn1j5zhm3.png)
![\cos \theta=(x)/(√(x^2+y^2))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yb4vl6l34evxhqriutx1x9bkirbvfpkbq9.png)
and
![\tan \theta=(y)/(x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5hba6hhwsyj28633ub9pj44ur2tvy2pwth.png)
1)
![P(-(1)/(2),(√(3))/(2))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rmolpcr1kbmcuw43ro183mqy4cu7ykfhnk.png)
as x-value is negative and y-value is positive.
Hence, the point lie in the second quadrant.
Also,
![x=-(1)/(2)\ ,\ y=(√(3))/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lf46jfydqgoglqful5w7aln156sqzenlpv.png)
Hence,
![√(x^2+y^2)=\sqrt{((-1)/(2))^2+((√(3))/(2))^2}\\\\\\√(x^2+y^2)=\sqrt{(1)/(4)+(3)/(4)}\\\\\\√(x^2+y^2)=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pmxdno5e95w302kztikodcksua5aka9tgv.png)
Hence, we have:
- and
![\tan \theta=((√(3))/(2))/((1)/(2))\\\\\\\tan \theta=√(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gkha39mh8bn1jal10y6g6i985564nxkguh.png)
2)
P(0,-1)
As x-value is zero and y-value is negative.
Hence, the point lie on negative y-axis.
Also,
![x=0\ ,\ y=-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gh6h5z4rbh9bli7r0iv3er582btmfwvdqx.png)
Hence,
![√(x^2+y^2)=√((0)^2+(-1)^2)\\\\\\√(x^2+y^2)=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/i1xijanxlw5sl9j51zdzflsen9wehrl2ks.png)
Hence, we have:
- and
,
Hence, we have: tan θ= undefined
3)
![P(-(√(2))/(2),-(√(2))/(2))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3qlbf32bsc0d9na7cyzevahrac70fv16sz.png)
which is same as:
![P(-(1)/(√(2)),-(1)/(√(2)))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bb0haizl31ys4arnl4q19sdlqzdz1vcweg.png)
As both the points are negative, hence the point lie in the third quadrant.
Also,
![x=(-1)/(√(2))\ ,\ y=(-1)/(√(2))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rrs532yn67v9xzpgka1u4zf50fdglmx8g6.png)
Hence, we have:
![√(x^2+y^2)=\sqrt{((-1)/(√(2)))^2+((-1)/(√(2)))^2}\\\\\\√(x^2+y^2)=\sqrt{(1)/(2)+(1)/(2)}\\\\\\√(x^2+y^2)=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dwe6svn8n1j9vhiwykbwfggqalk1kipf41.png)
Hence, we have: